2001
DOI: 10.1023/a:1013046322993
|View full text |Cite
|
Sign up to set email alerts
|

Translating research findings to PTSD prevention: Results of a randomized–controlled pilot study

Abstract: Based on therapeutic studies revealing positive prognostic factors and on research findings revealing how trauma is processed, we developed the memory structuring intervention (MSI) in attempt to prevent posttraumatic stress disorder (PTSD). The MSI attempts to shift processing of traumatic memory from uncontrollable somatosensory and affective processes to more controlled linguistic and cognitive processes by providing patients organization, labeling, and causality. In a single-blind randomized-controlled pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 26 publications
0
37
0
2
Order By: Relevance
“…In a study yielding data comparable to those of , Gidron et al (2001) developed a two-session CBT intervention that was intended to promote memory reconstruction among individuals who had been involved in traffic accidents. The intervention was delivered over the telephone from 1 to 3 days after the accident.…”
Section: Cbt For Asdmentioning
confidence: 99%
“…In a study yielding data comparable to those of , Gidron et al (2001) developed a two-session CBT intervention that was intended to promote memory reconstruction among individuals who had been involved in traffic accidents. The intervention was delivered over the telephone from 1 to 3 days after the accident.…”
Section: Cbt For Asdmentioning
confidence: 99%
“…For example, a study by Gidron 29 reported that women participating in a given intervention had a lower frequency of PTSD symptoms than men taking part in the same intervention 29 , which contrasts with previous results from the same group 14 .…”
Section: Other Types Of Psychological Interventionmentioning
confidence: 69%
“…Results were divided according to the type of intervention (pharmacological or psychological). From the 29 articles reviewed, 16 reported significant effects of interventions for the prevention of PTSD or symptoms related to the disorder [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Of these, 22 studies used psychological interventions and 7 used pharmacological interventions (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations